New social interactions: Ways of understanding the flow of communication in organizations and daily life [Nuevas interacciones sociales: Formas de entender el flujo de la comunicación en las organizaciones y la cotidianidad] (2015)
This paper introduces some of the main elements that configure a paradigm shift in Communication, with the aim of providing a reflection on the ever-changing nature of both the World and our discipline. This is the time for publics and audiences; they embody the message's sense and its raison d'être. The present paper collects the results of two different research studies conducted at different times and with diverse actors and audiences, applying the eclectic method. Some of these findings are as follows: communication has changed due to the appearance of new screens (media) and new actors, who have now become "citizen celebrities". The Twenty First Century has arrived, bringing with it changes to our old paradigms. The new subjects act and live together in cyberspace; they select their own media and develop their own content. Reality is not really virtual, but it is enriched by these new screens (new media). Copyright © 2015 (Mauricio Andrés Alvarez Moreno and Luis Horacio Botero Montoya).